Targeting pituitary adenylate cyclase-activating polypeptide (PACAP) with monoclonal antibodies in migraine prevention: a brief review. (1st November 2020) - Rustichelli, Cecilia; Lo Castro, Flavia; Baraldi, Carlo; Ferrari, Anna
ABSTRACT: Introduction: Interest is growing in the role of pituitary adenylate cyclase-activating polypeptide (PACAP) and its specific PAC1 receptor in migraine and in their antagonism as a strategy for migraine prevention. Areas covered: We discuss and critically evaluate (i) the evidence of the role of PACAP in migraine pathophysiology and (ii) the first clinical trials in migraine prophylaxis with monoclonal antibodies AMG 301 and ALD1910 which act against PAC1 and PACAP38 respectively. We examined PubMed, Scopus, and ClinicalTrials.gov electronic databases to examine the relevant material. Expert opinion: There is much proof of the ability of PACAP to cause migraine, but there is limited evidence that blocking PACAP or PAC1 receptor can prevent migraine. However, the potential of anti-PACAP antibodies in migraine prophylaxis is high. Theoretically, if these antibodies block the activation of the trigeminovascular system, they will prevent the onset of migraine attacks. There are still knowledge gaps in the role of PACAP in migraine and the risk/benefit ratio of anti-PACAP antibodies must be carefully studied.